1997
DOI: 10.1128/jvi.71.1.284-290.1997
|View full text |Cite
|
Sign up to set email alerts
|

Plasma viremia in macaques infected with simian immunodeficiency virus: plasma viral load early in infection predicts survival

Abstract: A reliable method for the quantitation of plasma viremia in nonhuman primates infected with simian immunodeficiency virus (SIV) and related viruses is described. This method is based on an established quantitative-competitive PCR format and includes a truncated control for internal assay calibration. Optimization of assay conditions has significantly improved amplification specificity, and interassay variability is comparable to that of commercially available assays for human immunodeficiency virus (HIV) quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
64
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(83 citation statements)
references
References 28 publications
(40 reference statements)
16
64
0
2
Order By: Relevance
“…In particular, baseline viral load shortly after acute infection (or 'viral load set point') has been shown to be highly prognostic for progression to AIDS [18][19][20] and is generally considered one of the best markers for disease progression in HIV seroconverters [21,22]. Similar results have been obtained in macaque challenge studies [23,24]; moreover, experimental interventions that reduced set point have been shown to delay disease progression [9,10,25]. Viral load has also been shown to be highly predictive of infectiousness [26] such that a vaccine's e ect on early viral load may also be a reasonable surrogate of VE I .…”
Section: Introductionmentioning
confidence: 61%
“…In particular, baseline viral load shortly after acute infection (or 'viral load set point') has been shown to be highly prognostic for progression to AIDS [18][19][20] and is generally considered one of the best markers for disease progression in HIV seroconverters [21,22]. Similar results have been obtained in macaque challenge studies [23,24]; moreover, experimental interventions that reduced set point have been shown to delay disease progression [9,10,25]. Viral load has also been shown to be highly predictive of infectiousness [26] such that a vaccine's e ect on early viral load may also be a reasonable surrogate of VE I .…”
Section: Introductionmentioning
confidence: 61%
“…''upregulated protein; ''N'', no difference; ''*'', failed identification Analysis of the virus load revealed high levels of viral RNA copies in spleen tissue at 7, 14, and 21 dpi, indicating the development of persistent infection. The virus load reflects the status of viral replication and disease evolution, and it has therefore been used as an important marker for disease progression of retroviral infections [57,74]. Thus, it is conceivable that the virus copy numbers observed in the present study would be indicative of a high level of infection.…”
Section: Discussionmentioning
confidence: 79%
“…Nonhuman primate models are invaluable for advancing our understanding of virus-host interactions and disease pathogenesis, and none has been more informative in this regard than the simian immunodeficiency virus (SIV) model of human immunodeficiency virus (HIV) infection. Experimental SIV infection of rhesus macaques and other Asian nonhuman primate species results in progressive disease similar to HIV infection in humans, although with an accelerated course of decline; SIV infection of rhesus macaques is therefore a key model to study AIDS pathogenesis [1][2][3][4][5]. In contrast, SIV infection in "natural" African nonhuman primate hosts of SIV, such as the African green monkey and sooty mangabey, is nonpathogenic, and disease does not generally develop despite productive virus replication.…”
Section: Nonhuman Primate Models Of Human Immunodeficiency Virus Infementioning
confidence: 99%